USING ENGLISH VIDEO CONVERSATION â€œASKING AND GIVING OPINIONâ€ TO IMPROVE STUDENTSâ€™ SPEAKING ABILITY - Ningsih, Fatma; Ikhsanudin, Ikhsanudin; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed at improving the eighth- grade students of SMP N 2 Pontianak speaking ability in Academic Year 2017/2018. This research used English video conversation "asking and giving opinion" in teaching speaking. The method of the research was the classroom action research, which consisted of 2 cycles. The subject of this research was the students of class 8F of SMP N 2 Pontianak in academic year 2017/2018. The result of this research showed that the students? speaking ability in each cycle has improved during their activity in the asking and giving opinion. The technique of data collection in this research  observation. The tools of data collection are a recorder, a observation checklist, and a field note. The result of data analysis showed that the students' speaking ability improved after the process the teachers drilling the students' pronunciation continuously and applying vocabulary practice using English video conversation "asking and giving opinion". Keywords: English Vide Conversation ?Asking and Giving Opinion?,Speaking, Classroom Action Research